Administration of live-attenuated vaccine of Vibrio harveyi to improve survival of gnotobiotic brine shrimp (Artemia salina) model against multipleVibrio infection - Chin, Yong Kit; Al-saari, Nurhidayu; Mohd-Aris, Aslizah; Zamri-Saad, Mohd; Md Yasinb, Ina Salwany (INTERNATIONAL NETWORK NATURAL SCIENCES-INNSPUB, 2019)
Newly developed live-attenuated protease derivative from pathogenic Vibrio harveyis train Vh1 as a live vaccine to against Vibriosis of aquatic animals. In the current study, we used the gnotobiotic A. salina as model to evaluate the safety and efficacy of the live-attenuated. This study was conducted by bacterial safety experiment and bacterial efficacy experiment. During the bacterial safety, the wild type and live-attenuated of V. harveyi (MVh-vhs) were tested for 48 hours on the Artemia larvae (instar II). During the efficacy experiment, the A. salina larvae were incubated with different concentration of live-attenuated V. harveyi (MVh-vhs), then challenged with V. harveyi, V. alginolyticus and V. parahaemolyticus. The result of safety experiment showed that the high concentration of live-attenuated mutant V. harveyi (MVh-vhs) at concentration of 109 CFU/mL is safe and had improved the A. salina larvae survival compared to other groups. On the other hand, pathogenic wildtype V. harveyi caused lethal effect on A. salina larvae by decreasing their survival. The surprising result of efficacy experiment showed that 107 CFU/mL of live attenuated MVh-vhs with 6 hours post incubation withA. salina larvae contributed higher survival while 109 CFU/mL of live attenuated MVh-vhs with 24 hours incubated A. salina larvae contributed higher survival against multiple Vibrio challenge. In this study, we concluded that the incubation time had affect bacterial concentration uptake by A. salina larvae and affect the effectiveness of Artemia bioencapsulation for targeted hosts.